Analisis Strategi Pemasaran Bank Syariah Indonesia dalam Meningkatkan Pangsa Pasar Melalui Pemanfaatan Teknologi Informasi - Zuhrinal M. Nawawi; Faris Andrawika Harahap (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study uses a qualitative method with a case study approach to analyze the marketing strategies employed by Bank Syariah Indonesia (BSI) in increasing market share through the utilization of information technology. In the rapidly evolving digital era, the use of information technology has become a crucial factor for Islamic financial institutions to reach a wider customer base and provide more effective and efficient services. This study examines how BSI integrates digital technology into its marketing strategies, including the use of online platforms, mobile banking applications, and social media for product education and promotion. The findings reveal that the utilization of information technology not only improves service accessibility but also strengthens customer relationships through more personal and responsive interactions. This strategy contributes to increased customer loyalty and expands BSI’s market share amid competition in the Islamic banking industry. This study provides valuable insights for developing digital marketing in the Islamic financial sector that is adaptive to technological advancements.